Model Pemangku Kepentingan dalam Keberhasilan Proyek - Herry Pintardi Chandra; Indarto .; I Putu Artama Wiguna; Peter F. Kaming (Jurnal Teknik Industri: Jurnal Keilmuan dan Aplikasi Teknik Industri, 2011)
Stakeholder condition is particularly important to reach project success. The objective of this study is to investigate the stakeholder conditions which are suggested in three parts; stakeholder impact, stakeholder engagement, and stakeholder psychological empowerment on project success. The data obtained from a questionnaire survey administered to 197 respondents for initial research, 204 for main research, and 5 construction companies for validation research by using structural equation modeling (SEM) with program AMOS 16. The results indicated that stakeholder psychological empowerment applying of the ability to perform has a significant influence on project success measured by quality performance. On the other hand, stakeholder engagement reflected by engagement scope has no significant influence on project success